Effects of cultivation methods on some soil biological parameters of a meadow chernozem soil (Vertisols) - Oláh Zsuposné, Ágnes (Acta Agraria Debreceniensis, 2010)
The effect of extended drought conditions on soil, the unfavourable cultivation technologies and the application of chemicals have been enhancing the processes of physical and biological soil degradation, so the fertility of soil is gradually declining. The effects of two cultivation methods – traditional ploughing (TP) and conservation tillage (CT) – on the biological activity of a meadow chernozem soil were examined in a long term experiment. Different parameters of the biological activity of soil were determined. These are the numbers of total bacteria, microscopic fungi, aerobic cellulose decomposing bacteria, as well as the activities of some important soil enzymes and CO2 production. Conservation tillage seemed to be a more favourable cultivation method for the majority of microorganisms, the activities of urease and dehydrogenase enzymes and CO2 production, compared to the traditional ploughing system. These parameters increased significantly, especially in the upper layer of conservation tillage plots. Concerning the plant cultures, the majority of microbiological parameters were higher in the soil of vetch (Vicia sativa L.) depending on the cultivation methods, so involving the pulses to the crop-rotation seems to be very important in this soil type. According to the ninth year’s results, the importance of conservation tillage as a means of protecting the soil biological activity in meadow chernozem (Vertisols) can be established; it was proven by microbiological investigations.